ANTIOXIDANT-PROOXIDANT AND CYTOKINE BALANCE IN THE LATE PERIOD OF COMBINED TRAUMA IN THE EXPERIMENT - Hudyma, A.A.; Kashchak, T.V.; Shepitko, K.V. (World of Medicine and Biology, 2019)
The purpose of the study was to determinethe antioxidant-prooxidant and cytokine balance in the late period of combined trauma in the experiment.The total of 90 non-linear white rats, 180-200 grams weight, which were on a standard vivarium diet were used in the experiments. All animals were divided into four groups: control and three experimental. In the first experimental group, under the conditions of thiopental-sodium anesthesia (40 mg per 1 kg body weight intraperitoneally), a moderate severity of closed trauma was modeled and caused a closed fracture of the femoral bones. In the second experimental group was modeled skin burns III A-B degree 10-11% of the body surface – to the depilated surface of the back skin, was applied 28 sm2 copper plate pre-immersed in boiling water for 3-5 minutes. In the third experimental group these two injuries were combined. The control group included intact animals.The surviving animals, in conditions of thiopental-sodium anesthesia (80 mg per 1 kg of body weight intraperitoneally), after 14, 21, 28 days after trauma were taken out from the experiment.In the liver homogenate, the reagentc on tent was determined for thiobarbituric acid (TBC-active products) and catalase based on which the antioxidant-prooxidant index (API = catalase / TBC-active products) was calculated. In addition, the contentof IL-1α and IL-4 was determined in blood serum using flow cytometry.It has been established that in the late period of traumatic disease (14-28 days), in the conditions of simulated injuries, stay imbalance prooxidant-antioxidant mechanisms and the formation of pro- and anti-inflammatory cytokines is violated.Their amplitude and vector depend on the origin of the injury. Under the conditions of isolated skeletal trauma, the API undergoes a second reduction after 21 days, indicating the re-domination of the prooxidant mechanisms for the deficiency of the antioxidant defen sesystem. Under these conditions, the content of serum IL-1α and IL-4 gradually decreases, and after 28 days the content of the studied indices is significantly lower than in the control. After simulation of burns, the antioxidant-prooxidant balance violation is maximal after 14 days with further recovery, which does not reach control level until 28 days. Under the seconditions, as compared with control group, the content of serum IL-1α is gradually increased and the content of IL-4 is moderately elevated. After the modeled combined trauma, the maximum violations of the antioxidant-prooxidant balance were observed. In this group, the entire period of observation was dominated by pro-oxidant mechanisms. After 21 and 28 days, the API value was significantly lower, compared to other experimental groups. A similar dynamics was observed in the serum levels of IL-1α, while the content of IL-4 in serum was significantly highein all terms.In the condition of a combined trauma, the period of late manifestations of traumatic desease is accompanied by significant violations of the antioxidant-prooxidant and cytokine balance, manifested by a significant decrease of PI. Against the background of lowering the serum content of pro inflammatory cytokine IL-1α and increasing the anti-inflammatory IL-4, this is an adverse reaction to injury and indicates a reduction in the recovery of the epidermis and the barrier properties of the skin as a whole.
Keywords: combined trauma; late period; antioxidant-prooxidant balance; cytokines